Seroprevalence of Dengue Virus and rickettsial infections in Cambodian children - Fox-Lewis, A; Hopkins, J; Sar, P; Sao, S; Pheaktra, N; Day, NPJ; Blacksell, SD; Turner, P (American Society of Tropical Medicine and Hygiene, 2019)
Scrub typhus (ST, Orientia tsutsugamushi), murine typhus (MT, Rickettsia typhi), and dengue virus (DENV) are important causes of childhood morbidity in Cambodia. This prospective, cross-sectional, seroprevalence study determined the proportion of Cambodian children infected by these pathogens and the ages at which initial infection is likely to occur. A total of 993 patient serum samples were tested for MT- and ST-specific IgG, and 837 samples tested for DENV-specific IgG. Overall, ST, MT, and DENV seroprevalence was high, estimated at 4.2%, 5.3%, and 50.7%, respectively. Scrub typhus and MT seropositivity peaked in children aged 8-11 and 12- to 15 years, respectively, suggesting initial infection occurs in these ages. Dengue virus seroprevalence steadily increased with age, indicating constant DENV exposure. The results of this study suggest that in Cambodian children presenting with undifferentiated febrile illness, dengue should be considered high in the list of differential diagnoses, and empirical anti-rickettsial antimicrobial therapy may be more indicated in 8- to 15-year-olds.